Academic Skills Guidance Efforts to Reduce Plagiarism Act in Student Writing in The Digital Age at Krisnadwipayana University – Jakarta - Gunawan Widjaja (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
ABSTRACTThis article aimed to interview seven academics related to academic skill instructions to reduce student plagiarism in academic writing in the digital era. To complete the data, we have conducted a series of data searches, the first being an electronic search for data on several publications and literature related to the theme of this study and interviewing seven academics to ask for their views on the guidance and training provided to students at the Krisnadwipayana university in Jakarta. After the data has been collected both in the literature and the results of interviews, we then enter into data analysis under the phenomenological approach, namely an attempt to understand something phenomenal among the existing data so that we can conclude the results as valid findings. Based on the search for data and the results of interviews, we can conclude that academic efforts at the University of Jakarta in combating plagiarism by students include training and punishments for those caught committing plagiarism. Plagiarism training is emphasized understanding and technical guidance methods for students to be able to carry out academic writing activities that are free from plagiarism elements. Thus, it is hoped that these findings will become a treasured knowledge of additional scientific studies and support future projects. Keywords: Academic Skill, Reduce Plagiarism, Academic Writing, Digital Age. ABSTRAKArtikel ini bertujuan untuk mewawancarai tujuh akademisi terkait instruksi keterampilan akademik untuk mengurangi plagiarisme mahasiswa dalam penulisan akademik di era digital. Untuk melengkapi data tersebut, kami telah melakukan serangkaian pencarian data, yang pertama adalah pencarian data elektronik pada beberapa publikasi dan literatur yang terkait dengan tema penelitian ini dan mewawancarai tujuh akademisi untuk meminta pandangan mereka tentang bimbingan dan pelatihan yang diberikan kepada mahasiswa Universitas Krisnadwipayana Jakarta. Setelah data terkumpul baik dalam literatur maupun hasil wawancara, selanjutnya kita masuk ke dalam analisis data dengan pendekatan fenomenologis, yaitu upaya untuk memahami sesuatu yang fenomenal di antara data yang ada sehingga dapat kita simpulkan hasilnya sebagai temuan yang valid. Berdasarkan penelusuran data dan hasil wawancara, dapat disimpulkan bahwa upaya akademik dalam mengurangi tindakan plagiarisme oleh mahasiswa meliputi pelatihan dan sangsi bagi mereka yang kedapatan melakukan plagiarisme. Pelatihan plagiarisme ditekankan pada pemahaman dan metode bimbingan teknis anti plagiat agar mereka dapat melaksanakan kegiatan penulisan akademik yang bebas dari unsur plagiarisme. Dengan demikian, diharapkan temuan ini akan menjadi pengetahuan berharga untuk studi ilmiah tambahan dan mendukung proyek-proyek masa depan. Kata Kunci: Kemampuan Akademik, Mengurangi Plagiarisme, Penulisan Akademik, Era Digital.